Sodium/iodide Symporter Mutant V270E causes stunted growth but no cognitive deficiency - Nicola, Juan Pablo (2015)
Iodide (I−), an essential constituent of the thyroid hormones, is actively accumulated in the thyroid by the Na+/I− symporter (NIS), a key plasma membrane protein encoded by the slc5a5 gene. Mutations in slc5a5 cause I− transport defects (ITDs), autosomal-recessive disorders in which I− accumulation is totally or partially impaired, leading to congenital hypothyroidism. The characterization of NIS mutants has yielded significant insights into the molecular mechanism of NIS.